Potential benefit of vitamin D supplementation in people with respiratory illnesses, during the COVID‐19 pandemic - Vasudevan V. Chetty (Wiley, 2021)
Abstract This review describes the evidence for the potential benefit of vitamin D supplementation in people with respiratory diseases who may have a higher susceptibility to coronavirus disease 2019 (COVID‐19) infection and its consequences. Clinical evidence indicates that vitamin D may reduce the risk of both upper and lower respiratory tract infections and offers benefit particularly in people with vitamin D deficiency. Some evidence exists for a higher incidence of active tuberculosis (TB) in patients who are deficient in vitamin D. An association between low levels of 25(OH)D (the active form of vitamin D) and COVID‐19 severity of illness and mortality has also been reported. In addition, low 25(OH)D levels are associated with poor outcomes in acute respiratory distress syndrome (ARDS). The cytokine storm experienced in severe COVID‐19 infections results from excessive release of pro‐inflammatory cytokines. Due to its immunomodulatory effects, adequate vitamin D levels may cause a decrease in the pro‐inflammatory cytokines and an increase in the anti‐inflammatory cytokines during COVID‐19 infections. Vitamin D deficiency was found in 82.2% of hospitalized COVID‐19 cases and 47.2% of population‐based controls (p < 0.0001). The available evidence warrants an evaluation of vitamin D supplementation in susceptible populations with respiratory diseases, such as TB, and particularly in those who are deficient in vitamin D. This may mitigate against serious complications of COVID‐19 infections or reduce the impact of ARDS in those who have been infected.